Weight increase in people with cystic fibrosis on CFTR modulator therapy is mainly due to increase in fat mass - Marialena Mouzaki; Annie Dupuis; Julie Avolio; Katherine Griffin; Felix Ratjen; Elizabeth Tullis; Tanja Gonska (Frontiers Media S.A., 2023)
Background: Ivacaftor, the first CFTR modulator drug, leads to significant long-term improvement in lung function and weight gain. The mechanism as well as the long-term impact of ivacaftor on weight, resting energy expenditure (REE) and body composition remains to be explored.Methods: This prospective observational study included 18 people with CF (pwCF) (age: median (range) 20 (6-58) years) carrying at least one CFTR gating mutation commencing ivacaftor. Assessments of body composition, REE and laboratory investigations were performed at baseline and 6, 12 and 24 months after treatment initiation.Results: Treatment with ivacaftor was associated with a significantly positive change in BMI z-score at 24 months. Fat mass (mean (95% CL) of 6.5 kg (4.0; 9.0) from baseline, p = 0.0001), but not fat-free mass changed under ivacaftor treatment. There was a significant positive correlation between weight and fat mass change. Overall, there was no significant change in measured REE from baseline (mean (95% CL) of 108 kcal/d (−12; 228), p = 0.07) in our cohort. Pancreatic function and other nutritional markers did not change with treatment, with the exception of an increase in serum vitamin A levels (p = 0.006).Conclusion: The weight gain observed in ivacaftor treated pwCF is predominantly secondary to increases in fat mass warranting early counseling of people starting on CFTR-modulating treatment with respect to healthy diet and physical exercise.